Ludwig van Beethoven : musical pioneer - Greene, Carol (Chicago : Childrens Press, 1989)
A biography of Beethoven who lived a stormy life and wrote great music.
Includes index.
School Library Journal.
3.2
K-3
Keywords: Beethoven, Ludwig van, -- 1770-1827 -- Juvenile literature; Beethoven, Ludwig van, -- 1770-1827.; Beethoven, Ludwig van, -- 1770-1827.; Composers -- Austria -- Biography -- Juvenile literature; Composers; Austrian composers -- Biography